2013
DOI: 10.1068/a4574
|View full text |Cite
|
Sign up to set email alerts
|

Noxious Neighbours? Interrogating the Impacts of Sex Premises in Residential Areas

Abstract: Premises associated with commercial sex-including brothels, striptease clubs, sex cinemas, and sex shops-have increasingly been accepted as legitimate land uses, albeit ones whose location needs to be controlled because of assumed 'negative externalities'. However, the planning and licensing regulations excluding such premises from areas of residential land use are often predicated on assumptions of nuisance that have not been empirically substantiated. Accordingly, this paper reports on a survey of those livi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 38 publications
0
31
0
Order By: Relevance
“…Instead of pom shops, Dundas Street West is now lined with wholesome and organic food purveyors" (Kaminer, 2009). In this narrative, transformation is accomplished as ideas about 'dirty' work and 'dirty' workers intra-act with and produce the neighbourhood's 'withering', while wholesome consumption practices become its saviour (Hubbard et al, 2013). Gentrification is cast not as a turf war between working-class residents and middle-class newcomers, but as a war between sex workers and vegan restaurants-in other words, between two types of seemingly very different embodied consumption practices.…”
Section: Displacing the Dirtymentioning
confidence: 97%
“…Instead of pom shops, Dundas Street West is now lined with wholesome and organic food purveyors" (Kaminer, 2009). In this narrative, transformation is accomplished as ideas about 'dirty' work and 'dirty' workers intra-act with and produce the neighbourhood's 'withering', while wholesome consumption practices become its saviour (Hubbard et al, 2013). Gentrification is cast not as a turf war between working-class residents and middle-class newcomers, but as a war between sex workers and vegan restaurants-in other words, between two types of seemingly very different embodied consumption practices.…”
Section: Displacing the Dirtymentioning
confidence: 97%
“…In this sense, notions of class, immorality and deviance were connected via the materialization of lap dance clubs in the landscape, leading to in situ reactions based on notions of disgust (see also Sibley, ). This implies that while most claim they are not opposed to sexual entertainment venues in general terms, when such clubs become visible in particular settings they can arouse widely shared concerns and anxieties (cf Hubbard et al ., ). This geographically informed perspective on disgust suggests that the interpretation of respectable standards of behaviour and comportment is something that needs to be understood relationally and contextually, with the transgression of ‘civilized’ standards of comportment mapped onto specific places and objects.…”
Section: Vibrant Clubs or A Vulgar Presence?mentioning
confidence: 97%
“…The suggestion here is that those claiming to belong to the ‘respectable classes’ do this by complaining about, and dissociating themselves from, the excessive and vulgar behaviour they associate with the faction of the working classes that is disrespectful and ill‐mannered (Tomsen, ). Inevitably, this is mapped onto space, and finds in expression in NIMBY (‘Not in My Back Yard’) protests against ‘sex premises’ (Hubbard et al ., ): our respondents hence frequently spoke of customers as failing to recognize local norms of behaviour, and disturbing community ways of life:
The club is a venue for the binge‐drinkers who is [ sic ] seeking drugs and prostitution: their loud behaviour, screaming, shouting, swearing, running echoes round the streets. Empty bottles, broken glass vomit and urine can be seen around the pavement in this area.
…”
Section: Gentlemen or ‘Unsavoury’ Males?mentioning
confidence: 99%
“…Our survey found that residents across both these areas were far less aware of the existence of a commercial sex premises within their local area (56.9%, 228 out of 401) than they were of other known types of commercial premises such as cafes/restaurants (91.8%, 368 out of 401) and pubs/bars and clubs (88.0%, 353 out of 401). In addition, of those aware of sex premises, nearly half (49%, 112 out of 228) evaluated the impact as neutral, while there were nearly as many respondents rating the impact positively (24%, 55 out of 228) as negative (27%, 62 out of 228) (see Hubbard et al ., ).…”
Section: Community Awareness and Perceptions Of Offensementioning
confidence: 97%